Measurable journalism digital platforms, news metrics and the quantified audience - Carlson, Matt 1977- (Routledge, 2021)
This book explores ways in which the increasingly 'measurable' news audience has had an impact on journalistic practices, in an era when digital platforms provide real-time, individualizable, quantitative data about audience consumption practices. Considering the combination of digital technology that makes measurable journalism possible, the contributors to this volume examine the work of various actors involved in aspects of measurable journalism both inside and outside the newsroom and confront the normative implications of the data-centric trends of measurable journalism. Including examples from across the globe, the book balances hopes for increased engagement or impact with fears that economic prioritization will hurt journalism's standing in the public sphere.This book will be of interest to those studying journalistic practices in the modern world, as well as those studying media consumption and emerging digital technologies. This book was originally published as a special issue of Digital Journalism
Keywords: Internet; Nachricht; Journalismus